Analisis Risiko Investasi terhadap Return Saham pada Sub Sektor Makanan dan Minuman di Bursa Efek Indonesia - Anas Tesya Br Sitepu; Ihsan Effendi; Eka Dewi Setia Tarigan (Universitas Medan Area, 2020)
The purpose of this study was to determine the Investment Risk Analysis of Stock Returns in the Food and Beverage Sub Sector in the Indonesia Stock Exchange. This type of research is quantitative. The data source used in this study is secondary data. Data collection techniques using judgment sampling in food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX). The data analysis technique used in the study is simple regression analysis with IBM SPSS version 21.0. Hypothesis testing results state that Investment / Market Risk has a positive and significant effect on Stock Returns on food and beverage companies on the Indonesia Stock Exchange. This can be explained that if the investment risk is higher, then stock returns will also be higher in the company during the research year.